Coupling effects of surface building and earthquake loading on in-service shield tunnels. (January 2021) - Liu, Hongqing; Liu, Huabei; Zhang, Yeqin; Zou, Yan; Yu, Xiaobo
Abstract: In a dense urban environment, an in-service shield-tunnel is very likely to be subjected to additional loading from later-built surface structures, which could couple with the earthquake effects and aggravate the seismic damages of the tunnel structures. The main objective of this study aims at investigating the coupling effects of later-built surface building and earthquake loading on in-service subway shield tunnels. To this end, a series of numerical studies are carried out, employing a Finite Element model in which the segment joints and connecting bolts are simulated. The surface structure is assumed to be a 10-storey three-span reinforced concrete frame on a raft foundation. Some critical indexes, including lining deformation, dynamic lining forces, joint displacement, as well as the mechanical response of the joint bolt are used to evaluate the coupling effects. As a comparison, the responses without the surface building and those with tunnel ling simplified as equivalent continuous rings are also investigated. The results reveal that the coupling effects lead to much higher seismic response of the tunnel structure. The location of the surface building plays an important role on the seismic responses, which increase and then decrease with an increase in the distance s that is measured from the center of the surface building to the tunnel axis.